The criteria for nominating gifted coordinators in public and private schools and their effects on talent sustainability: A mixed study - Alhassan, Albandary Abdullah; Alarfaj, Abdulhamid (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the criteria used for selecting talent coordinators in public and private schools, as well as to determine the differences between these schools in applying these criteria. Additionally, it sought to identify the internal and external obstacles affecting the sustainability of talent nurturing from the coordinators’ perspective. A mixed-methods approach was employed, with a random sample of 138 coordinators, including 51 from private schools and 87 from public schools. The results indicated that the most commonly applied criteria for selecting talent coordinators in public schools included personal traits such as flexibility, while in private schools, it was the ability to recognize gifted students. No statistically significant differences were found between the schools in applying these criteria. The main obstacles affecting the sustainability of talent nurturing in public schools were a lack of qualified staff, while in private schools, it was non-compliance with selection criteria. Statistically significant differences were found in these obstacles favoring private schools. The qualitative findings aligned with the quantitative results, revealing two types of selection: self-selection by the coordinators and external selection by the school. The interviews identified both internal and external obstacles to sustaining talent nurturing. Based on the findings, the study recommended the widespread dissemination of selection criteria and the provision of training programs for talent coordinators, as well as raising awareness among families about the importance of participation in talent nurturing programs.